Optical properties of amorphous Ba0.7Sr0.3TiO3 thin films obtained by metal organic decomposition technique - Xu, Zhimou; Tanushi, Yuichiro; Suzuki, Masato; Wakushima, Keita; Yokoyama, Shin (Thin solid films, 2006)
Barium strontium titanate (BaxSr1−x)TiO3 (BST) thin film deposition techniques are the subjects of many research studies mainly due to their influence on the optical and electrical properties of this material, which are of increasing interest for the processing of optoelectronic integrated circuits. In this study, the amorphous Ba0.7Sr0.3TiO3 (BST0.7) thin films were grown onto fused quartz and silicon substrates at low temperature by using a metal organic decomposition (MOD)-spin-coating procedure from barium 2-caprylate Ba(C8H15O2)2 and 3-methylbutyl acetate CH3COOC2H4CH(CH3)2-based special precursors. The optical constants of amorphous BST0.7 thin films including refractive index, extinction coefficient and optical band gap energies were presented. The calculated extinction coefficient of 214-nm-thick amorphous BST0.7 thin films in visible and near-infrared region was in the order of 10−3, which is much lower than that of polycrystalline BST thin films. The optical band gap energy and refractive index n are estimated to be about 4.27 eV and n=1.94, respectively. The optical propagation loss of the groove optical waveguide with 10 μm width and 185-nm-thick amorphous BST0.7 films was 4.11 dB/cm at a wavelength of 632.8 nm.